2021
DOI: 10.1111/1467-8500.12531
|View full text |Cite
|
Sign up to set email alerts
|

What is in a form? Examining the complexity of application forms and administrative burden

Abstract: Analysis of the welfare state emphasises that access to social security support is a key component of the relationship between the state and the citizen. Recent literature has identified administrative burden as a concept that helps us to understand an emerging dynamic between the state and the citizen, where citizens must deal with increasingly onerous administrative 'costs' in order to access services or support from the state.Increased administrative burden has been identified at many stages of access to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…On the other hand, men are more likely to be diagnosed with conditions that have more straightforward paths to NDIS access—such as autism and intellectual disability, which form the bulk of the scheme (NDIS, 2019: 6). Recent research has found that the NDIS application form is very long and administratively burdensome, with many questions that can be difficult to answer for those with complex lives or fluctuating support needs (Brown et al, 2021). Our findings suggest that some women are aware of these difficulties and may be deterred from applying as a result.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, men are more likely to be diagnosed with conditions that have more straightforward paths to NDIS access—such as autism and intellectual disability, which form the bulk of the scheme (NDIS, 2019: 6). Recent research has found that the NDIS application form is very long and administratively burdensome, with many questions that can be difficult to answer for those with complex lives or fluctuating support needs (Brown et al, 2021). Our findings suggest that some women are aware of these difficulties and may be deterred from applying as a result.…”
Section: Discussionmentioning
confidence: 99%
“…I tried to design the form with prompts for applicants to include information relevant to a claim that may assist a decision maker in considering all relevant factors. Brown et al, (2021) analyse the concept of 'administrative burden' through research on a certain form in a growing body of scholarship on bureaucratic forms. They look at the barriers to and levels of complexity in completing a particular form.…”
Section: Reflection On Design Choicesmentioning
confidence: 99%
“…In each area of administration particular issues can arise due to the contextual nature of public administration and the nature of the power being exercised by bureaucrats (Donson and O'Donovan, 2015). Other variables include what different entities need to register; plurality of system users (Brown et al, 2021); literacy levels; the significance of what is at stake; legal representation; whether a form is being used at first instance or on appeal; where a form is being filled in or submitted (van der Valk and Rogan, 2023); digitalisation of forms (Tomlinson, 2019;Tomlinson, 2020;Tomlinson and Meers, 2022) and institutional culture (Thomas, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Administrative burden has been explored in different streams of research, including business environments (Liao, 2020 ), street-level bureaucracy (Bell et al, 2021 ), red tape (Brown et al, 2021 ), and government program management (Keiser & Miller, 2020 ). Moynihan and colleagues (Moynihan et al, 2015 ) first conceptualized administrative burden as three categories of costs that individuals experience in citizen–government interactions, including learning, compliance, and psychological costs.…”
Section: Literature Review and Theoretical Hypothesesmentioning
confidence: 99%
“…In addition, the self-service process on social media and online platforms lowers the chances of experiencing negative feelings due to burdensome face-to-face contact with street-level bureaucracy. Furthermore, digital platforms allow the submission of digital instead of paper materials (Brown et al, 2021 ), thereby reducing compliance costs.…”
Section: Literature Review and Theoretical Hypothesesmentioning
confidence: 99%